Marcha de acúmulo de matéria-seca e de nutrientes pelo milho superdoce - Meneses, Natália Barreto [UNESP] (2014)
Brazil has high potential for the production of sweet corn (Zea mays L. ssp. Mays), aimed principally at industrial processing. It is important that happens a good fertilizer management and mineral nutrition for the ears reach the standard processing. Therefore, this study aimed to quantify the growth and nutrient uptake by maize hybrid supersweet GSS 41243. An experiment was conducted in Guaira-SP, Brazil, in the period April to August 2013, using a completely randomized design, with nine treatments that correspond to the times of collection of plants (20, 30, 40, 50, 60, 70, 80, 90 and 100 days after emergence) and four replications. Picking up ten plants per replication in each sample, which were divided into leaf, stem, tassel and ear. Were determined accumulations of macro (N, P, K, Ca, Mg, S) and micronutrients (B, Cu, Mn, Fe and Zn) in each part of the plant in each collection time. The total nutrient uptake by the crop was 306.8; 46.2; 406.3; 39.0; 33.4 and 23.1 kg ha-1 of N, P, K, Ca, Mg and S, respectively, and 213.6; 118.4; 3360.0; 784.0 and 684.0 g ha-1 Cu, Fe, Mn and Zn, respectively. Dynamics of nutrient accumulation by supersweet corn followed the descending order: K> N> P> Ca> Mg> S> Fe> Mn> Zn> B> Cu. The export of nutrients that corresponded to the amounts present in the ear at the time of the last collection, that is, the R3 stage, were in the order of 103.0 kg ha-1 N; 19.0 kg ha-1 P; 104.5 kg ha-1 K; 3.4 kg ha-1 of Ca; 9.90 kg ha-1 and 7.3 kg Mg ha-1 S, 64.0 g ha-1 B; 33.6 g ha-1 of Cu; 632 g ha-1 of Fe; 184 g ha-1 of Mn and 320 g ha-1 Zn